2004
DOI: 10.1167/iovs.03-1380
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hemangiogenesis and LymphangiogenesisafterNormal-Risk Corneal Transplantation by Neutralizing VEGF Promotes Graft Survival

Abstract: There is concurrent, VEGF-A-dependent hem- and lymphangiogenesis after normal-risk keratoplasty within the preoperatively avascular recipient bed. Inhibition of hem- and lymphangiogenesis (afferent and efferent arm of an immune response) after normal-risk corneal transplantation improves long-term graft survival, establishing early postoperative hem- and lymphangiogenesis as novel risk factors for graft rejection even in low-risk eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
275
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 301 publications
(291 citation statements)
references
References 27 publications
4
275
0
12
Order By: Relevance
“…Both preexisting corneal BVs and LVs are important risk factors for immune‐mediated allograft rejection after high‐risk keratoplasty 4, 31, 38. Therefore, it is mandatory to regress preexisting corneal vessels in high‐risk eyes before transplantation, and mature BVs and LVs have become new therapeutic targets to enhance surgical success rates after corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both preexisting corneal BVs and LVs are important risk factors for immune‐mediated allograft rejection after high‐risk keratoplasty 4, 31, 38. Therefore, it is mandatory to regress preexisting corneal vessels in high‐risk eyes before transplantation, and mature BVs and LVs have become new therapeutic targets to enhance surgical success rates after corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic corneal transplantation was performed as previously described31, 32 to compare the long‐term graft survival between the CXL group and controls. Twenty‐four female BALB/c mice were used as recipients, and 12 female C57BL/6 mice were used as corneal donors.…”
Section: Methodsmentioning
confidence: 99%
“…Penetrating corneal transplantation was performed after suture removal. Keratoplasty was performed as described previously (37). Donor corneas were excised by trephination using a 2-mm bore, and cut with curved Vannas scissors.…”
Section: Corneal Transplantationmentioning
confidence: 99%
“…VEGF-A induces both angiogenesis and lymphangiogenesis by binding to the VEGF receptor 1 (VEGFR1) and VEGFR2, although the latter process is mainly driven via the binding of VEGF-C and VEGF-D to VEGFR2 and VEGFR3 (Carmeliet and Jain 2000). It has been reported that blocking the corneal lymphatic vessels that flow directly to the DLNs is effective in preventing allograft rejection Cursiefen et al 2004;Bachmann et al 2008). Recently, two important findings in the cornea have reported that a soluble form of VEGFR1 (sVEGFR1) acts as a potent natural inhibitor of corneal angiogenesis, and a soluble form of VEGFR2 (sVEGFR2) prevents lymphangiogenesis and maintains an alymphatic cornea (Ambati et al 2006;Albuquerque et al 2009).…”
Section: Introductionmentioning
confidence: 99%